Dynamics of forest deforestation in the amazon of pará: an approach centered in space econometry - CARVALHO, André Cutrim (International Journal of Development Research, 2023)
This article aims to theoretically discuss the main factors responsible for the dynamics of forest clearing in the Amazon of ofPará, an approach perspective performed through spatial econometrics. The basic hypothesis is that the expansion of the agricultural frontier is the conductive element from forest deforestation phenomenon in Pará. In this context, the spatial econometrics served as an extremely important tool to measure, from the results obtained in spatial econometric model the effects that the forest clearing has led in Pará. The main conclusion is that the increased expansion of cattle ranching in the Amazon frontier driven by demand from abroad has directly influenced the increase of deforestation, hindering the development of sustainable activity in the region.The period chosen for the spatial econometric analysis covers the years 2000 and 2008 due to high forest deforestation rate in the state of Pará.